2008
DOI: 10.1080/02640410701501697
|View full text |Cite
|
Sign up to set email alerts
|

Reference values and improvement of aerodynamic drag in professional cyclists

Abstract: The aims of this study were to measure the aerodynamic drag in professional cyclists, to obtain aerodynamic drag reference values in static and effort positions, to improve the cyclists' aerodynamic drag by modifying their position and cycle equipment, and to evaluate the advantages and disadvantages of these modifications. The study was performed in a wind tunnel with five professional cyclists. Four positions were assessed with a time-trial bike and one position with a standard racing bike. In all positions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
107
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(120 citation statements)
references
References 33 publications
6
107
1
6
Order By: Relevance
“…Positions that resulted in reductions in aerodynamic drag were also related to a lower velocity deficit and turbulence levels in the wake. Studies by García-López et al [51] and Underwood et al [49] have shown that reducing the torso angle generally results in a reduction in aerodynamic drag. However, these studies also showed that minimising torso angle did not always lead to the lowest aerodynamic drag readings.…”
Section: Wind Tunnel Testing Of Rider Positionmentioning
confidence: 99%
See 2 more Smart Citations
“…Positions that resulted in reductions in aerodynamic drag were also related to a lower velocity deficit and turbulence levels in the wake. Studies by García-López et al [51] and Underwood et al [49] have shown that reducing the torso angle generally results in a reduction in aerodynamic drag. However, these studies also showed that minimising torso angle did not always lead to the lowest aerodynamic drag readings.…”
Section: Wind Tunnel Testing Of Rider Positionmentioning
confidence: 99%
“…The effectiveness of rider equipment, such as bicycles and helmets, is also dependent on the position and type of rider [51,[63][64][65]. For these reasons, the most effective method to optimise a cyclist's aerodynamic performance to date has largely been through a trial-and-error approach to force measurements in a wind tunnel.…”
Section: Wind Tunnel Testing Of Rider Positionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, due to the rather high velocity (in the order of 50 km/h), the aerodynamic resistance acting on a time-trial racer is about the 90% of the total resistance. Aerodynamics is thus very important for the cyclists performances and many experimental studies, addressed to find the best cyclist position as well as the best articles, have been carried out in the past (Garcia-Lopez et al, 2008;Gibertini & Grassi, 2008;Grappe et al, 1997;Lukes et al, 2005). Furthermore, although they are outside of the subject of the present treatise, some interesting computational works begin to appear in literature (see for example Defraeye et al (2010a;).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile common aerodynamic drag coefficient values for bicycles can range from 0.6 to 0.8 in racing configurations [5]. Previous research by field testing and wind-tunnel experiments by Garcia-Lopez et al [6] showed that adjustments to the cyclist's position, even minor ones, can result in a decrease of the aerodynamic drag, which indicates the possibility for optimization. In summary, previous research has shown that helmet aerodynamics can play a significant role in performance and that production helmets do not perform well at decreased pitch angles.…”
Section: Introductionmentioning
confidence: 99%